UMPSA receives the 2023 Low Carbon City Award - Hazlina, Faizal (UMPSA, 2024)
KUALA LUMPUR, 7 February 2023 - Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) made history by receiving the 2023 Low Carbon City Award at the 2023 Malaysia Low Carbon City Award Ceremony.